Time to deconstruct the concepts of “foreplay” and “intercourse”: the real structure of human sexual encounters - Monge-Nájera, Julian; Rodriguez, Mariana; Gonzalez, Maria Isabel (UNED Research Journal, 2017)
Historically, the study of sexual behavior has been affected by diffuse concepts such as foreplay and coitus; the unreliability of self reports; and Eurocentrism. Here we deal with those problems and present data on frequency of sexual positions and stopwatch measurements of foreplay activities from direct observation of video recordings by 604 heterosexual Latin American couples.The most frequent positions were “woman on her hands and knees”; “woman on bed with man standing”, and “woman sitting on man”. The most frequent activities were fellatio; manual stimulation of the penis; and manual stimulation of the vulva. The longest mean durations of particular activities were 67 seconds for coitus, 37 s for fellatio and 34 s for petting. These frequency results differ from reports from the USA, possibly because of cultural differences but more probably because our results are based on what the couples actually do (rather on what they report, as in the American studies). Previous studies have merged a complex variety of sexual activities into a single imprecise category called “foreplay” and ours seems to be the first study to “deconstruct” foreplay into its individual components, and to use objective measurements of their duration